A Performance Analysis of General Packet Radio Service (GPRS) and Narrowband Internet of Things (NB-IoT) in Indonesia - Bima, I Wayan Krisnhadi; Suryani, Vera; Wardana, Aulia Arif (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2020)
Internet of Things (IoT) refers to a concept connecting any devices onto the internet. The IoT devices cannot only use a service or server to be controlled at a distance but also to do computation. IoT has been applied in many fields, such as smart cities, industries, and logistics. The sending of IoT data can use the existing GSM networks such as GPRS. However, GPRS is not dedicated particularly to the transmission of IoT data in consideration of its weaknesses in terms of coverage and power efficiency. To increase the performance of the transmission of IoT data, Narrowband-IoT (NB-IoT), one alternative to replace GPRS, is offered for its excellence in coverage and power. This paper aims to compare the GPRS and NB-IoT technology for the transmission of IoT data, specifically in Bandung region, Indonesia. The results obtained showed that the packet loss from clients for the GPRS network was at 68%, while the one for NB-IoT was at 44%. Moreover, NB-IoT technology was found excellent in terms of battery saving compared to GPRS for the transmission of IoT data. This result showed that NB-IoT was found more suitable for transmitting the IoT data compared to GPRS.